2005
DOI: 10.1111/j.1745-4514.2005.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sarcoplasmic Proteins and Their Interaction With Myofibrillar Proteins

Abstract: The protein solubility and molecular‐weight distribution of freeze‐dried sarcoplasmic proteins (SPs) from rockfish treated under low and high pH as well as various NaCl concentrations were elucidated. The solubility of SPs was significantly suppressed at an acidic pH (2.0–4.0) and in the presence of high salt concentration (0.5 M NaCl). The least amount of protein was lost when SPs were treated at pH 2.0 or 3.0 followed by precipitation at pH 5.5. The interaction of SPs with Alaska pollock surimi (myofibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 30 publications
7
80
1
Order By: Relevance
“…While the protein concentrate is mainly composed by myofibrillar protein and a small fraction of sarcoplasmic protein (DihortGarcia et al, 2011), the mantle mince is composed of all the muscle proteins. In this sense, different authors described that during sol-gel transition, sarcoplasmic proteins coagulate and adhere to myofibrillar proteins, making difficult the formation of gels (Kim et al, 2005). This is one of the reasons it is difficult to develop strong and elastic gels from pelagic species (Choi and Park, 2002) characterized by a high content of sarcoplasmic proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the protein concentrate is mainly composed by myofibrillar protein and a small fraction of sarcoplasmic protein (DihortGarcia et al, 2011), the mantle mince is composed of all the muscle proteins. In this sense, different authors described that during sol-gel transition, sarcoplasmic proteins coagulate and adhere to myofibrillar proteins, making difficult the formation of gels (Kim et al, 2005). This is one of the reasons it is difficult to develop strong and elastic gels from pelagic species (Choi and Park, 2002) characterized by a high content of sarcoplasmic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that it is more than likely due to the action of transglutaminase on the sarcoplasmic proteins. However, the muscle of cephalopods contains little endogenous transglutaminase activity and it is necessary to use a microbial transglutaminase isolated from microorganisms (Streptoverticilium) (Pérez-Mateos et al, 2004;Kim et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Chicken surimi thermogram normally contained two endothermic transitions. Referring to previous DSC studies of similar (Figure 3) samples (Sych et al 1990(Sych et al , 1991Herrera & Mackie 2004;Kim et al 2005;Thawornchinsombut & Park 2006), it can be assumed that the two peaks in this study are related to the thermal denaturation of myosin and actin. The data related to thermal transition temperatures (t p ) of myosin and actin are presented in Table 1.…”
Section: Results and Discusionmentioning
confidence: 63%
“…For instance, Farouk et al (2002) reported that sarcoplasmic proteins are important in determining the cohesiveness of cooked sausage batter. Results from Kim et al (2005) showed that the inclusion of sarcoplasmic proteins positively contributed to the gelation properties of myofi brillar proteins (surimi).…”
Section: Creatine Kinase and Meat Qualitymentioning
confidence: 99%